Pengaruh Etos Kerja Dan Human Relation Terhadap Kinerja Karyawan PT Albany Corona Lestari Mengwi Badung - Dewi, Ni Luh Gede Novita; Ayu Wimba, I Gusti; Mashyuni, IA (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
This study aims to determine how the influence of work ethic and human relation on employee performance at PT Albany Corona Lestari Mengwi Badung. This research was conducted at PT Albany Corona Lestari Mengwi Badung with the number of respondents taken as many as 45 employees. Data was collected through observation, interviews, documentation, literature, and questionnaires. The data analysis technique used is multiple linear regression model. Based on the results of the study, it was found that: (1) the effect of work ethic on performance was positive and significant, (2) the influence of human relation on performance was positive and significant, (3) the effect of work ethic and human relation on performance was positive and significant. Suggestions that can be given in this study are PT Albany Corona Lestari Mengwi Badung needs to develop a work system, provide training to employees in providing excellent service to clients and provide employees with completing work.